2011
DOI: 10.1007/s11244-011-9745-3
|View full text |Cite
|
Sign up to set email alerts
|

Lab Scale Fixed-Bed Reactor for Operando X-Ray Absorption Spectroscopy for Structure Activity Studies of Supported Metal Oxide Catalysts

Abstract: Lab scale fixed-bed reactor is applied for operando transmission X-ray absorption spectroscopy (XAS) for structure-activity studies of supported metal oxide catalysts under real reaction conditions. This setup includes many properties of an optimal fixed-bed reactor for operando transmission XAS studies. For instance, it is usable in a wide range of temperature (up to 1,000°C), pressure and space velocity. Besides, this operando setup can be used for transmission XAS measurements in a wide edge energy range. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Similar approaches for the application of intermediate X-ray energies have been developed by other scientists. 154,155 O'Brien et al achieved spatiotemporal mapping of a catalytic reactor supported on translational stages by using various a Precautions should be taken to avoid contact when using Be windows especially at high temperatures. spectroscopic techniques.…”
Section: High Energy Radiationmentioning
confidence: 99%
“…Similar approaches for the application of intermediate X-ray energies have been developed by other scientists. 154,155 O'Brien et al achieved spatiotemporal mapping of a catalytic reactor supported on translational stages by using various a Precautions should be taken to avoid contact when using Be windows especially at high temperatures. spectroscopic techniques.…”
Section: High Energy Radiationmentioning
confidence: 99%
“…19,24,25 Furthermore, in order to reduce mass transfer resistances across the catalyst bed and to derive reliable intrinsic kinetic data, the operando cells must be capable of handling high space velocities. 26,27 Different configurations of operando and in situ reactor cells have been reported. [28][29][30][31][32][33][34] Among these, it is common to find modified Harrick cells, which have been used for combined DRIFTS and XAS studies.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, different configurations were reported as alternatives. 27,36,37 Among these, Chiarello et al demonstrated a spectroscopic cell for in situ transmission XAS with DRIFTS. 36 In this design, the X-ray and IR beams were focussed on the same optical window and were perpendicular to the catalyst bed.…”
Section: Introductionmentioning
confidence: 99%